System and method for color palette translation - White, Brian K (2002)
A portion of the disclosure of this patent document contains material which is subject to copyright protection. The copyright owner has no objection to the facsimile reproduction by anyone of the patent document or the patent disclosure, as it appears in the Patent and Trademark Office patent files or records, but otherwise reserves all copyright rights whatsoever. The system and software of the present invention presents a process for translating a source palette containing TV unsafe colors into a resultant modified palette containing only TV safe colors, while preserving the color trends in the source palette. The software will first analyze a source color palette to determine the TV unsafe colors contained therein. For each TV unsafe color in the source color palette, the software determines the closest TV safe color by selecting a TV safe color that is the shortest Euclidean distance from the TV unsafe color. The TV unsafe colors are substituted with the calculated TV safe colors and stored in the resultant palette. The software will divide the color space of the source palette into discrete regions, e.g., by Hue (H), by selecting reference colors as the boundaries of the regions. The initially TV safe color will then be modified in a manner similar to the modifications made on nearby reference colors that were required to make them TV safe. The result will be a resultant palette comprised of only TV safe colors that maintains the color trends of the source palette when perceived by the human eye.